Heart of glass : a novel - Landis, Jill Marie (Landis, Jill Marie. Irish angel series, 2011)
When Colin forces Kate to promise his dying sister that together they will care for his niece and nephew, she complies. Having been orphaned herself, Kate realizes she must put the children's welfare above her own-- even if it means a marriage of convenience. Can her persistent love and faith transform their uncertain future?